2011
DOI: 10.1016/s0140-6736(10)61967-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of circumcision of HIV-negative men on transmission of human papillomavirus to HIV-negative women: a randomised trial in Rakai, Uganda

Abstract: Background Randomized trials show that medical male circumcision (MC) reduces high-risk human papillomavirus (HR-HPV) infection in men. We assessed the efficacy of MC to reduce HR-HPV in female partners. Methods HIV-negative men were randomized to immediate MC (intervention) or MC delayed for 24 months (control). HIV-uninfected female partners of married men (648 intervention and 597 control arm) were simultaneously enrolled and provided interview information and self-collected vaginal swabs at baseline, 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
149
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(152 citation statements)
references
References 30 publications
1
149
2
Order By: Relevance
“…There is also good evidence from randomized controlled trials that male circumcision is associated with a lower prevalence of human papillomavirus (HPV) infection 31,32 and herpes simplex virus type 2 (HSV-2) transmission, 31,33 as well as a decreased likelihood of bacterial vaginosis (BV) in female partners. 80 The evidence for male circumcision being protective against syphilis is less strong, [65][66][67][68] however, and male circumcision was not found to be associated with decreased risk of gonorrhea 84,85,91-93 or chlamydia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also good evidence from randomized controlled trials that male circumcision is associated with a lower prevalence of human papillomavirus (HPV) infection 31,32 and herpes simplex virus type 2 (HSV-2) transmission, 31,33 as well as a decreased likelihood of bacterial vaginosis (BV) in female partners. 80 The evidence for male circumcision being protective against syphilis is less strong, [65][66][67][68] however, and male circumcision was not found to be associated with decreased risk of gonorrhea 84,85,91-93 or chlamydia.…”
Section: Resultsmentioning
confidence: 99%
“…In the Uganda randomized controlled trial, the prevalence of high-risk HPV infection was 28% lower in female partners of circumcised HIV-uninfected men, while the incidence was 23% lower. 32 Good evidence from another Uganda randomized controlled trial of male circumcision in HIV-infected men indicates that a circumcision did not reduce the risk of male-to-female transmission of high-risk HPV from HIV-infected men. 103 …”
Section: Gonorrheamentioning
confidence: 99%
“…1 Circumcision is generally considered as a simple, rapid operation with efficacy for protection against HIV and other sexually transmitted infections, as confirmed in numerous, highquality studies. [2][3][4][5][6][7] Circumcision has been reported to adversely affect sexual function; 8 however, the majority of studies, including highquality ones [9][10][11] and ones with data arising from randomized controlled trials (RCTs), 12,13 show no difference or improvement in sexual function, sensitivity and satisfaction after circumcision. All of the data were considered by the American Academy of Pediatrics in formulating its 2012 policy, which concluded that there were no adverse effects on these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Two trials conducted on HIV positive and negative men in Uganda analyzed transmission of HPV to female partners [101,102]. The implications of reduced HPV infection in female partner cervical cancer rates are not clearly discernible since there are several other confounding risk factors.…”
Section: Hpv In Female Partnersmentioning
confidence: 99%
“…In the first trial on HIV negative men and their partners, the year-2 prevalence of HR-HPV infection in partners was 28% in the circumcised group and 39% in the uncircumcised group (PRR 0.72, 95% CI 0.60-0.85) [101]. The incidence of any HR-HPV infection between 0 and 2 years was also lower in the circumcised group female partners (IRR 0.77, 95% CI 0.63-0.93).…”
Section: Hpv In Female Partnersmentioning
confidence: 99%